1998
DOI: 10.1071/ea97087
|View full text |Cite
|
Sign up to set email alerts
|

Responses to grain feeding by grazing dairy cows

Abstract: Summary. Two experiments were conducted on feeding grain supplements to dairy cows during summer. In experiment 1, dairy cows in mid–late lactation were offered one of 2 pasture allowances (about 20 and 40 kg DM/cow.day) with and without a supplement of a grain mix (5 kg of a 70 : 30 mixture of barley and lupins). This experiment was conducted twice over 2 consecutive summer–autumn periods (years 1 and 2). Milk yields were higher at the high pasture allowance and with grain feeding. The marginal response to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
39
0
11

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 18 publications
9
39
0
11
Order By: Relevance
“…Cows consuming only pasture had a NUE of 21.0 ± 6.1% while supplemented grazing cows improved their NUE, storing in the milk 24.6 ± 3.8% of the ingested N, showing a positive effect of CHO supplementation on NUE (Van Vuuren et al, 1993;Berzaghi et al, 1996;Carruthers and Neil, 1997;Robaina et al, 1998;Reis and Combs, 2000;Walker et al, 2001;Bargo et al, 2002;Steinshamn et al, 2006). This improvement may be due to a decrease in CP content of the diet and to an increase of microbial protein synthesis.…”
Section: Strategies To Improve N Use Efficiency In Grazing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows consuming only pasture had a NUE of 21.0 ± 6.1% while supplemented grazing cows improved their NUE, storing in the milk 24.6 ± 3.8% of the ingested N, showing a positive effect of CHO supplementation on NUE (Van Vuuren et al, 1993;Berzaghi et al, 1996;Carruthers and Neil, 1997;Robaina et al, 1998;Reis and Combs, 2000;Walker et al, 2001;Bargo et al, 2002;Steinshamn et al, 2006). This improvement may be due to a decrease in CP content of the diet and to an increase of microbial protein synthesis.…”
Section: Strategies To Improve N Use Efficiency In Grazing Systemsmentioning
confidence: 99%
“…This improvement may be due to a decrease in CP content of the diet and to an increase of microbial protein synthesis. However, it is important to highlight that the improvement of NUE as a response to CHO supplementation occurs mainly when the pasture has a CP content higher than 200 g kg -1 (Van Vuuren et al, 1993;Berzaghi et al, 1996;Reis and Combs, 2000;Bargo et al, 2002); whereas with a lower CP content the effects are less important (Carruthers and Neil, 1997;O'Mara et al, 1997;Robaina et al, 1998;Walker et al, 2001;Steinshamn et al, 2006). Nevertheless, the highest reported values of NUE under grazing conditions are still lower than the ones obtained with cows fed total mixed rations (TMR), indicating that despite CHO supplementation there is still the possibility to develop other strategies that could improve NUE even more under grazing conditions.…”
Section: Strategies To Improve N Use Efficiency In Grazing Systemsmentioning
confidence: 99%
“…Robaina et al (1998) found that milk responses to grain feeding in mid to late lactation cows grazing summer pastures ranged from 0.7 to 1.5 kg of milk/kg of grain consumed, depending on HA and level of grain fed. They suggested that pasture availability and quality seem to dominate responses to concentrate feeding under pasture-based systems.…”
Section: Stage Of Lactationmentioning
confidence: 99%
“…In addition, grain fed to dairy cows at levels greater than 6 kg DM/ cow per day may have detrimental effects on digestion in the rumen (Robaina et al 1998). High intakes of grain may reduce the digestion of forage and increase the amount of starch escaping digestion (Stockdale et al 1987).…”
Section: Stage Of Lactationmentioning
confidence: 99%
See 1 more Smart Citation